Misidentification of airflow obstruction: Prevalence and clinical significance in an epidemiological study - Pothirat C. (Dove Medical Press Ltd., 2015)
© 2015 Pothirat et al. Background: The fixed threshold criterion for the ratio of forced expiratory volume in the first second to forced vital capacity (FEV1/FVC),0.7 is widely applied for diagnosis of airflow obstruction (AO). However, this fixed threshold criterion may misidentify AO, because thresholds below the fifth percentile of normal FEV1/FVC (lower limit of normal; LLN) vary with age. This study aims to identify the prevalence of AO misidentification and its clinical significance. Materials and methods: A cross-sectional population-based study was conducted to identify the prevalence of chronic respiratory diseases in adults older than 40 years of age who live in municipal areas of Chiang Mai province, Thailand. All randomly selected subjects underwent face-to-face interviews and examinations by pulmonologists, and received chest radiographs and post-bronchodilator spirometry. AO misidentification was classified into under- or overestimated AO subgroups. Underestimated AO was defined as ratio of FEV1/FVC greater than the fixed threshold, but below the LLN criteria. Overestimated AO was defined as the ratio of FEV1/FVC below the fixed threshold but greater than the LLN criteria. The clinical significance of each misidentified subject was then explored. Results: There were 554 subjects with a mean age of 52.9±10.1 years and a percent predicted FEV1 of 85.5%±15.4%. The prevalence of AO misidentification was 5.6% (31/554), and all subjects belonged to the underestimated subgroup. Clinical significance of underestimated subjects included clinical AO disease of 22.6% (7/31) (three subjects with chronic obstructive pulmonary disease [COPD] and four subjects with asthma); chronic respiratory symptoms of 54.8% (17/31) (mostly associated with chronic rhinitis, 70.6% [12/17]); and only 12.9% (4/31) were identified as non-ill subjects. Conclusion: The prevalence of AO misidentification in this population was significant, and all were underestimated subjects. Most underestimated subjects had clinical significance as related to obstructive airway diseases and chronic respiratory symptoms, mostly associated with rhinitis.